Global Operations Innovativeness and Entrepreneurship at 3M Company Limited - Sakyi, Kwesi Atta (Advances in Social Sciences Research Journal, 2019)
This paper examines 3M Company’s supply chain operations globally as well as its operational challenges in doing business in a developing country. 3M is a US-based company that is noted for its many innovative inventions and products. The objective of this paper is to evaluate best practices in terms of sustainability and entrepreneurial innovation. The paper adopts a purely desk-based secondary research approach by reviewing existing literature to make inferences and to throw light on some challenges experienced in supply chain management. The paper concludes that companies that incorporate sustainable principles into their operations ensure their survival and also they gain competitive advantage over their rivals.